Effectiveness of a flexible coiled sheath for correcting an acute angle between the brachiocephalic vein and the superior vena cava for successful defibrillator implantation - Yeon Pyo Yoo (Journal of Arrhythmia, 2012)
Successful implantation of implantable cardioverter-defibrillators (ICDs) that is performed to avoid surgery in patients with atypical vasculature is still problematic. Acute angulations and significant tortuosity of the venous vasculature may influence both procedural success and periprocedural complications. We successfully implanted an ICD in a patient with deformed vasculature caused by tuberculosis-induced lung destruction by using a flexible coiled sheath instead of a friable peel-away sheath. This report highlights an alternative maneuver that may be an option in patients who have an acute angle between the brachiocephalic vein and the superior vena cava.